Effectveness inactivation of trypsin inhibitor from brazilian cultivars of beans (Phaseolus vulgaris L.) - Paiva, Kelli Cristina [UNESP]; Carvalho, Maria Regina Barbieri de [UNESP]; Pizauro Júnior, João Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The trypsin inhibitor, an antinutritional factor, which is abundant in dycotiledoneous and monocotyledoneous, is usually inactivated by heating treatment. The infl uence of pressure-cooking (121°C and 141kPa) for 30 min on, trypsin inhibitors concentration and inhibitors reactivation from ten Brazilian beans varieties of Phaseolus vulgaris L. namely: IAPAR-14, IAC-Carioca, Rudá, Corrente, IAC-Aruã, IAPAR-16, IAPAR-57, IACCarioca Pyatã, Carioca, Aporé, were investigated. The inhibitors reactivation was evaluated in comparison with the activity of raw and pressure-cooking. For raw the in vitro protein digestibility mean values ranged from 40% (in Carioca cultivar) to 60% (in IAC-Aruã cultivar), showing an increase from 11% to 37% using the autoclaving at 121°C and 141kPa. Among ten cultivars studied the trypsin inhibitor activity varied from 36.18UTI.mg-1 for IAC-Aruã to 63.33UTI.mg-1 for IAPAR-16. Trypsin inhibitor activity was totally inactivated by pressure-cooking. The study of the trypsin inhibitors reactivation using double-digestive pepsin-pancreatin enzymes in vitro showed a recovering activity from 34% up to 100%. Native inhibitor is resistant to double- digestive pepsin-pancreatin proteolysis, whereas autoclaving to 121o C.30 min-1 results in a non-native conformation that is susceptible to proteolysis, improving the digestibility and inactivate differentially the activity of trypsin inhibitors. The results of the thermal treatment of the beans show inactivation of the inhibitors, which may be due to formation of high molecular weight aggregates with other substances of the grain. The pepsin-pancreatin digestion of the inactivated inhibitor restores the activity, probably due to its retention by the digested fragments.

O inibidor de tripsina, um fator antinutricional abundante em dicotiledoneas e monocotiledoneas, geralmente é inativado pelo tratamento térmico. O efeito do cozimento a 121°C e 141kPa durante 30 minutos sobre a concentração do inibidor de tripsina e a reativação de dez cultivares brasileiras de feijão (Phaseolus vulgarisL.) denominadas IAPAR-14, IAC-Carioca, Rudá, Corrente, IACAruã, IAPAR-16, IAPAR-57, IAC-Carioca Pyatã, Carioca, Aporé foram investigados. A reativação dos inibidores foi avaliada em comparação com a atividade das amostras cruas e autocolavadas. A digestibilidade in vitro das proteínas variou de 40% (cultivar Carioca) a 60% (cultivar IACAruã), apresentando aumento de 11% a 37% com o aquecimento a 121°C e 141kPa. Dentre as dez cultivares estudadas a atividade do inibidor de tripsina variou de 36,18UTI. mg-1 para IAC-Aruã a 63,33UTI.mg-1 para o IAPAR-16. O inibidor de tripsina foi totalmente inativado pelo aquecimento a 121°C e 141kPa. O estudo de reativação da atividade dos inibidores de tripsina após digestão enzimática in vitro com as enzimas pepsina e pancreatina mostrou uma recuperação da atividade entre 34% a 100%. O inibidor na sua forma nativa é resistente a digestão simultânea das enzimas proteolíticas pepsina e pancreatina, enquanto o tratamento térmico a 121o C e 141kPa resulta em conformação susceptível a proteólise, melhorando a digestibilidade e inativando diferencialmente a atividade do inibidor de tripsina. Os resultados do tratamento térmico do feijão mostram a inativação dos inibidores, o que pode ser devido à formação de agregados de alto peso molecular com outras substâncias do grão. A digestão por pepsina-pancreatina do inibidor inativado recupera a atividade, decorrente de sua provável retenção pelos fragmentos digeridos.
Eficácia da inativação do inibidor de tripsina em cultivares brasileiras de feijão (Phaseolus vulgaris L.)
Keywords: Antinutritional factor; Heat treatment; In vitro protein digestibility; Inhibitor reactivation; Fator antinutricional; Tratamento térmico; Digestibilidade in vitro da proteína; Reativação do inibidor